Moral Intelligence of Senior High School Students in Bandung City as a Foundation for Developing Global Citizenship - Insani, Nisrina Nurul; Abdulkarim, Aim; Komalasari, Kokom; Rahmat, Rahmat; Anggraini, Diana Noor; Sopianingsih, Pitria (Newinera Publisher, 2025)
The moral intelligence development is becoming critical in equipping adolescents to be able to address the twenty first century ethical, societal and global challenges. This research analyzes the moral intelligence of high-school pupils in Bandung who are in their senior years with emphasis to four major aspects, which include integrity, responsibility, self-control and empathy. The quantitative design was conducted by use of a validated questionnaire that was administered at different grades. Data analysis was conducted using descriptive summaries, reliability test, confirmatory factor analysis, and inferential statistics conducted on the data (correlation and regression) to map the moral intelligence profiles of the students. The results have shown that the total moral intelligence is high, and empathy and self-control were found as the strongest areas, whereas integrity and responsibility exhibited lower scores. Internal consistency was measured by reliability and validity which confirmed that moral intelligence is multidimensional. The correlation analysis indicated that there were some significant interrelations between the dimensions, and regression indicated that empathy and self-control were the most effective predictors of the orientation of the students towards the global citizenship. There were also gender disparities in that female students scored higher in empathy whereas males exhibited a margin of self-control. Students were less consistent with regard to responsibility and integrity despite high sensitivity and behavioral regulation. The paper also identifies the necessity of experiential and digitally enriched, including service learning, digital citizenship programs, to reinforce weaker aspects and contribute to responsible and ethical involvement in the global environment.